Ao fim da cidade: conjuntos habitacionais nas bordas urbanas - Andre Luiz Prado de Oliveira (2014)
This thesis discusses the dialectical relationship established by population density in the urban limits of large Brazilian cities, materialized by multifamily housing projects meant for the poorest. For this, it analyzes the environmental condition of the social housing planned on a large scale at the edges of the metropolitan areas, and its immediate urban context, through a theoretical and empirical study. The main justification for this study, conducted at a time of renewed large-scale production of affordable housing on the edge of large cities, is the possibility to analyze, in social and environmental terms, the destiny fulfilled by the housing built more than three decades ago, under largest urban planning state control, over new housing, now mostly constructed by the private sector. The theoretical study has as starting point the definition of large vertical housing situated on the limits of the urban area in poor social and environmental condition as objects of study and then builds a theoretical framework based on three areas of discussion: the dialectic city / country in urban edges, seen in the perspective of critical theory and Marxist urban theory; the production of spatial injustice through formal housing production on a large scale on the outskirts of large cities; socio-environmental conflicts generated by the dialectical relationship between population and the environment. The theoretical reflection around these three axes organizes the empirical survey in nine sets on the limits of the urban concentration of Metropolitan Belo Horizonte, defining what data to be collected by the survey and how they should be organized. The information in empirical research, in turn, fueled a theoretical analysis on the environmental condition of the peripheral sets, structured by six analytical categories: the nature of urban edges; residents of the sets; peripheral intra-urban structures; modern housing development; environmental cumulative causation; urban political ecology. The main objective of the analysis was to determine whether the environmental situations of precariousness of large housing estates on the outskirts of urban areas are necessary or contingent and whether they are structural or circumstantial. The results of this reflection question the validity of modern housing built on the edge of the cities as a solution for the production of large-scale housing in Brazil.